Membangun Kesadaran Masyarakat untuk Menciptakan Lingkungan yang Efektif dalam Pananggulangan DBD serta Pengaplikasian K3 Guna Menciptakan Lingkungan yang Efektif - Marpaung, Albert Anggiat Petrus; Siregar, Barharuddin; Ramadhan, Firdaus; Hutauruk, Hendra Johanes; Lukman, Jihan Fadhilah; Naufal, Muhamad; Haulani, Muttharif Arrabie; Bahtiar, Nur Pajar Wahyu; Nugraha, Slamet; Mudrika, Dadan (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
The Community Service Program (KKN) Group 13 in Kelurahan Marga Mulya, Bekasi, aims to raise public awareness about the importance of maintaining environmental cleanliness and preventing Dengue Hemorrhagic Fever (DHF). This program includesvarious activities such as DHF prevention socialization, fogging activities to reduce mosquito populations, occupational health andsafety (K3) socialization, and community clean-up efforts. Program evaluation shows that active community participation andsupport from various parties greatly assist in achieving the program's goals. The sustainability of the program through ongoing training, cooperation with related institutions, regular monitoring and evaluation, infrastructure development, and environmentalcleanliness campaigns is recommended to ensure a reduction in DHF cases and an improvement in the community's quality of life.